FACTORS INFLUENCING THE SUCCESS OF EMPING MELINJO MICRO SMALL ENTERPRISE BASED ON CREATIVE ECONOMY IN ALUR GADUNG VILLAGE, SAWIT SEBARANG DISTRICT, LANGKAT DISTRICT - Sandi Pranata; Yusrizal Yusrizal; Budi Dharma (SEAN Institute, 2023)
The purpose of this study was to examine and analyze the effect of Raw Materials, Connections, and Promotion on the Success of Creative Economy-Based Micro, Small and Medium Enterprises Emping Melinjo Emping Melinjo in Langkat Regency. This research uses a quantitative descriptive approach and data is collected through questionnaires. The population in this study is the entire UMKM Industry in 2022 totaling 271 business actors, which are then used as a sample of 73 business actors. The data analysis tool used is the classic assumption method with multiple linear regression analysis, coefficient of determination, F test and t test. The results of this study indicate that: (1) Raw materials have a positive but not significant effect on business success. (2) Connection has a positive and significant effect on business success. (3) Promotion has a positive and significant effect on business success. And the value of the coefficient of determination (R2) is 0.529 which means that 52.9% of the variation in the value of business success is determined by four variables that influence business success, namely raw materials, connections, and promotions. While the rest (100% - 52.9% = 47.1%) is influenced by independent variables not examined.